2021
DOI: 10.1177/10556656211011896
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Lip and Palate in Infants With Prenatal Opioid Exposure

Abstract: Objective: This study examines phenotypic presentation and perioperative outcomes of cleft-related procedures for infants with cleft lip and/or palate (CL/P) and prenatal opioid exposure. Design: This is a retrospective review of infants with prenatal opioid exposure treated for CL/P from 2008 to 2018. Setting: Patients cared for at a tertiary center from 2008 to 2018. Patients/Participants: Eighteen patients with documented prenatal opioid exposure and CL/P had primary repairs in our unit. Main Outcome Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…Five patients classified as LTFU were found to have followed up shortly after the study period ended, further emphasizing the shortcomings of LTFU as a measure of compliance in long-term care. Although this study's rate of LTFU (13%) was lower than or comparable to those demonstrated in the literature (range, 9%-33%), DTFU rates were substantially higher (50%) 11,18,19 . This suggests that DTFU may be an earlier or more sensitive measure of decreased compliance that could help identify at-risk patients before they experience definitive negative consequences, such as delay of key interventions or LTFU.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Five patients classified as LTFU were found to have followed up shortly after the study period ended, further emphasizing the shortcomings of LTFU as a measure of compliance in long-term care. Although this study's rate of LTFU (13%) was lower than or comparable to those demonstrated in the literature (range, 9%-33%), DTFU rates were substantially higher (50%) 11,18,19 . This suggests that DTFU may be an earlier or more sensitive measure of decreased compliance that could help identify at-risk patients before they experience definitive negative consequences, such as delay of key interventions or LTFU.…”
Section: Discussioncontrasting
confidence: 53%
“…Although this study's rate of LTFU (13%) was lower than or comparable to those demonstrated in the literature (range, 9%-33%), DTFU rates were substantially higher (50%). 11,18,19 This suggests that DTFU may be an earlier or more sensitive measure of decreased compliance that could help identify at-risk patients before they experience definitive negative consequences, such as delay of key interventions or LTFU. We also found that patients with at least 1 NS were significantly more likely to have DTFU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations